Minimal surface scaffold designs for tissue engineering - Kapfer, Sebastian; Hyde, Stephen T.; Mecke, Klaus; Arns, Christoph H.; Schröder-Turk, Gerd (Biomaterials, 2011)
Triply-periodic minimal surfaces are shown to be a more versatile source of biomorphic scaffold designs than currently reported in the tissue engineering literature. A scaffold architecture with sheetlike morphology based on minimal surfaces is discussed, with significant structural and mechanical advantages over conventional designs. These sheet solids are porous solids obtained by inflation of cubic minimal surfaces to sheets of finite thickness, as opposed to the conventional network solids where the minimal surface forms the solid/void interface. Using a finite-element approach, the mechanical stiffness of sheet solids is shown to exceed that of conventional network solids for a wide range of volume fractions and material parameters. We further discuss structure property relationships for mechanical properties useful for custom-designed fabrication by rapid prototyping. Transport properties of the scaffolds are analyzed using Lattice-Boltzmann computations of the fluid permeability. The large number of different minimal surfaces, each of which can be realized as sheet or network solids and at different volume fractions, provides design flexibility essential for the optimization of competing design targets. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Bone tissue engineering; Finite element analysis; Mechanical properties; Scaffold; Rapid prototyping